Associação entre o estatuto socioeconómico, a prática de Atividade Física e a composição corporal em jovens adolescentes portugueses de ambos os sexos - Maria Helena Moura Araújo (2017)
Recognize and associate socio-economic status (SES) and levels of physical activity (PA) practiced, as well as finding a statistically significant correlation between the practice of PA and changes associated with body composition in young teenagers, was the aim of the study. The practice of physical activity is constrained and influenced by several factors and these are important to eliminate possible impediments. Thus, the work is based on two assumptions: (1) verify that there is an association between SES and levels of PA practiced; (2) what if the practice of regular PA associates with changes in body composition. A sample of 93 students (both genders) of basic and secondary school Airães, Felgueiras was studied, and standard procedures were used to collect age, height, weight, BMI, levels of PA and knowledge about PA. Inquiries were made about the household, of their students, including elements that composes, as the level of education, monthly income, general lack of health and social action level. SES was obtained through a questionnaire, as well as knowledge about PA. The main findings showed that there is a greater practice of PA in the social ranks with more support, including the 2/B, although it has been established that in all ranks found to exist the practice of PA. Also, it was found that the most frequent practices of PA are related to lower levels of % body fat (%BF).